The mediating role of attachment styles in the relationship between marital intimacy and self-differentiation in couples - Parsakia, Kamdin; Farzad, Valiolah; Rostami, Mehdi (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study aimed to investigate the mediating role of attachment styles in the relationship between marital intimacy and couples’ self-differentiation. Method: This research is descriptive-correlation type. The statistical population of the present study included all couples working in private offices in the 7th district of Tehran in 2022. Among these people, 100 couples (200 people) were selected by the available sampling method. In order to collect data, Collins’ (1996) Adult Attachment Style Questionnaire, Thompson and Walker’s (1995) Marital Intimacy Questionnaire and Skowron and Friedlander’s (1995) Self-Differentiation Inventory were used. Pearson’s correlation coefficient and regression analysis were used for the statistical analysis of the data. Results: The findings showed a direct relationship between marital intimacy and couples’ differentiation. Also, the results showed that attachment style moderates the relationship between marital intimacy and couples’ differentiation. Conclusion: Based on the findings, a secure attachment style can strengthen the relationship between marital intimacy and couples’ self-differentiation. Also, an insecure attachment style can weaken the relationship between marital intimacy and couples’ self-differentiation.